Accelerating Elementary School Teacher Performance in the Digital Era: The Contribution of Leadership, Collaboration, and Psychological Well-Being through Work Motivation - Heru Purnomo; Didi Supriadi; Saryanto Saryanto (CV. Edujavare Publishing, 2026)
The rapid development of digital technology has transformed the educational landscape, requiring schools to adapt to increasingly complex demands for effectiveness, innovation, and competitiveness. This study aims to analyze the contribution of leadership, collaboration, and psychological well-being to teacher performance through work motivation among elementary school teachers at SD Negeri Tlogodalem in the digital era. The study employed a quantitative approach using an explanatory survey design involving all teachers as respondents through a census sampling technique. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that leadership (β = 0.341; p < 0.001), collaboration (β = 0.296; p = 0.001), and psychological well-being (β = 0.412; p < 0.001) had significant positive effects on work motivation, explaining 72.4% of its variance (R² = 0.724). Furthermore, leadership (β = 0.254; p = 0.001), collaboration (β = 0.213; p = 0.003), psychological well-being (β = 0.318; p < 0.001), and work motivation (β = 0.402; p < 0.001) significantly influenced teacher performance, with the model explaining 78.1% of the variance in performance (R² = 0.781). Mediation analysis revealed that work motivation significantly mediated the relationships between leadership, collaboration, psychological well-being, and teacher performance. Among all predictors, psychological well-being emerged as the strongest factor affecting both work motivation and teacher performance. The findings suggest that enhancing teacher performance in the digital era requires an integrated strategy that strengthens effective leadership, promotes collaborative professional cultures, and supports teachers’ psychological well-being to foster higher work motivation and sustainable educational excellence.